Entre la competencia y la dependencia tecnológica: la nanotecnología en el continente americano - Delgado Ramos, Gian Carlo (Nómadas. Critical Journal of Social and Juridical Sciences, 2008)
The manipulation of matter at a billionth part of a meter, name it nanotechnology, is already one of the main technological development proposals of the XXI century. Still its notorious degree of uncertainty, nanotechnology development is escalating. And, because of its potentialities, the intercapitalist competence in such a niche is even more intense. The paper deals with this process from a socio-political and geoeconomical approach in order to acknowledge the dynamics and interests in stake; the power relations and networks; the real intercapitalist competence tensions and contradictions; etcetera. The evaluation focuses on the Occidental hemisphere nanotechnology agenda as an exercise that allows to illustrate, and assess, the main characteristics of high-technology development schemes within metropolitan economies (United States) in comparison with the case of the periphery ones (Latin America).